Trimethoprim-sulfamethoxazole as de-escalation in ventilator-associated pneumonia: a cohort study subanalysis - Strazzulla, Alessio (Eur J Clin Microbiol Infect Dis, 2021)
PURPOSE: This is a subanalysis of a previous study which compared the effectiveness of trimetoprim-sulfametoxazole (TMP-SMX) with all other regimens for treatment of ventilator-associated pneumonia (VAP). Aim of the current study was to focus on the effectiveness of a strategy based on TMP-SMX as de-escalation from β-lactam including regimens. METHODS: Retrospective cohort study including patients who were hospitalized for VAP from 2011 to 2019. Patients were distributed in two groups: NO SWITCH TO TMP-SMX group, including patients who received β-lactams for all treatment duration, and SWITCH TO TMP-SMX group, which included patients who switched to TMP-SMX from a β-lactam including regimen after microbiology diagnosis. Three clinical outcomes were analyzed: mortality at 30 days from the start of the antibiotic treatment (T30), mortality at the end of treatment (EoT), and acquisition of multidrug-resistant bacteria during hospitalization in intensive care unit. RESULTS: Overall, 70 patients were included in the current study, 32/70 (45.7%) in NO SWITCH TO TMP-SMX group and 38/70 (54.3%) in SWITCH TO TMP-SMX group, 37/70 (52.8%) had been already included in the previous study. No significant differences in clinical outcomes and patient’s characteristics were found when the two groups were compared. CONCLUSIONS: De-escalation to TMP-SMX for VAP treatment was not associated with higher mortality at EoT and T30 than standard treatment with β-lactam. Monotherapy with TMP-SMX as de-escalation from broad-spectrum empirical regimens is a β-lactam sparing strategy worthy to be further investigated in either multicenter cohort studies or randomized clinical trials.